2023
DOI: 10.3390/jcm12247540
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Work Assessment in Patients after Coronary Artery Bypass Grafting during Cardiac Rehabilitation

Francesco Perone,
Roberta Ancona,
Fausto di Stasio
et al.

Abstract: Background: Myocardial work is an innovative echocardiographic tool to assess left ventricular performance. Emerging data have shown the added value of this method for evaluating cardiac function compared to traditional echocardiographic parameters and global longitudinal strain. However, few studies are present in the literature about the role of myocardial work during cardiac rehabilitation. Our aim was to assess the impact of a rehabilitation program on myocardial work indices in patients with preserved lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The answer to this problem may be the use of new echocardiography techniques and more sensitive parameters of myocardial dysfunction in further research, especially in the individuals with preserved LVEF. Studies in recent years have shown that both global longitudinal strain and myocardial work can be early indicators of improvement in myocardial function after a cycle of physical training, independently of other clinical factors [52,53]. Their analysis in the context of physical performance could provide additional information influencing the overall management and prognosis assessment, especially in the group of patients who do not achieve significant clinical improvement after CR.…”
Section: Discussionmentioning
confidence: 99%
“…The answer to this problem may be the use of new echocardiography techniques and more sensitive parameters of myocardial dysfunction in further research, especially in the individuals with preserved LVEF. Studies in recent years have shown that both global longitudinal strain and myocardial work can be early indicators of improvement in myocardial function after a cycle of physical training, independently of other clinical factors [52,53]. Their analysis in the context of physical performance could provide additional information influencing the overall management and prognosis assessment, especially in the group of patients who do not achieve significant clinical improvement after CR.…”
Section: Discussionmentioning
confidence: 99%